Effects of directly autotransplanted tibial bone marrow aspirates on bone regeneration and osseointegration of dental implants. Issue 4 (23rd May 2013) - Payer, Michael; Lohberger, Birgit; Strunk, Dirk; Reich, Karoline M.; Acham, Stephan; Jakse, Norbert
Abstract Objectives Aim of the pilot trial was to evaluate applicability and effects of directly autotransplanted tibial bone marrow (BM) aspirates on the incorporation of porous bovine bone mineral in a sinus lift model and on the osseointegration of dental implants. Material and methods Six edentulous patients with bilaterally severely resorbed maxillae requiring sinus augmentation and implant treatment were included. During surgery, tibial BM was harvested and added to bone substitute material (Bio‐Oss®) at the randomly selected test site. At control sites, augmentation was performed with Bio‐Oss® alone. The cellular content of each BM aspirate was checked for multipotency and surface antigen expression as quality control. Histomorphometric analysis of biopsies from the augmented sites after 3 and 6 months (during implantation) was used to evaluate effects on bone regeneration. Osseointegration of implants was evaluated with Periotest® and radiographic means. Results Multipotent cellular content in tibial BM aspirates was comparable to that in punctures from the iliac crest. No significant difference in amount of new bone formation and the integration of bone substitute particles was detected histomorphometrically. Periotest® values and radiographs showed successful osseointegration of inserted implants at all sites. Conclusion Directly autotransplanted tibial BM aspirates did not show beneficial regenerative effects in the small study population (N = 6) of the present pilot trial. However, the proximal tibia proved to be a potential donor site for small quantities of BM. Future trials should clarify whether concentration of tibial BM aspirates could effect higher regenerative potency.